The putative forkhead transcription factor FhpA is necessary for development, aflatoxin production, and stress response in Aspergillus flavus - Jessica M. Lohmar; Stephanie R. Gross; Carol H. Carter-Wientjes; Brian M. Mack; Qijian Wei; Matthew D. Lebar; Jeffrey W. Cary (PLoS ONE, 2025)
Forkhead transcription factors regulate several important biological processes in many eukaryotic species including fungi. Bioinformatic analysis of the Aspergillus flavus genome revealed four putative forkhead transcription factor genes. Genetic disruption of (AFLA_005634), a homolog of the Aspergillus nidulans fhpA/fkhA gene (AN4521), revealed that the fhpA gene is a negative regulator of both asexual spore production and aflatoxin B1 production in A. flavus. Furthermore, disruption of the fhpA gene caused a complete loss of sclerotial formation. Overexpression of the fhpA gene caused A. flavus to become more sensitive to sodium chloride whereas disruption of the fhpA gene did not change the ability of A. flavus to respond to any osmotic stress agent tested. Interestingly, both disruption and overexpression of the fhpA gene led to increases in sensitivity to the oxidative stress agent menadione. Overall, these results suggest that fhpA is an important regulator of morphological and chemical development in addition to stress response in A. flavus.